Luz de agua. Una teoría de la electricidad entre los nahuas - Lorente Fernández, David (Revista Española de Antropología Americana, 2025)
This is a brief ethnographic text in which, using field materials collected by the author in two Nahua regions of Mexico, the conception that this group has of electricity is explored.